Thermophysical properties of Al-based metal matrix composites suitable for automotive brake discs - Lucia Lattanzi; Samuel Ayowole Awe (Journal of Alloys and Metallurgical Systems, 2024)
The present work investigates the effects of Ni, Cu, La, and Ce on the thermophysical properties of aluminium-based metal matrix composites. Transition metals and rare-earth elements were added to improve the mechanical performance of the material to above 420 °C, which is the maximum operating temperature of the reference material. In contrast, the addition of alloying elements results in the formation of intermetallic phases, Al3Ni and Al11(La,Ce)3, which, in turn, affect the thermal and physical properties of the base alloy. The goal is to apply the improved composites to automotive brake discs. The addition of alloying elements decreased the thermal conductivity by 20% and increased the stiffness by 90% at temperatures up to 470 °C. When stiffness and thermal conductivity are critical requirements, the addition of these alloying elements represents a valid solution.